2016
DOI: 10.1097/opx.0000000000000892
|View full text |Cite
|
Sign up to set email alerts
|

Optical Assessment of Soft Contact Lens Edge-Thickness

Abstract: Purpose To assess the edge shape of soft contact lenses using Gabor-Domain Optical Coherence Microscopy (GD-OCM) with a 2 μm imaging resolution in three dimensions, and to generate edge-thickness profiles at different distances from the edge tip of soft contact lenses. Methods A high-speed custom-designed GD-OCM system was used to produce 3D images of the edge of an experimental soft contact lens (Bausch + Lomb, Rochester NY) in four different configurations: in air, submerged into water, submerged into sali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…[77-83] Few studies have been carried out on ocular infections using ex vivo porcine eye models that had a mechanism to mimic the tear turnover. [78, 79, 83] Herein we designed an ex vivo porcine eye infection model, in which culture medium was dripped onto each eye at a rate of four 25 μL drops/min to represent the tear turnover in vivo.…”
Section: Resultsmentioning
confidence: 99%
“…[77-83] Few studies have been carried out on ocular infections using ex vivo porcine eye models that had a mechanism to mimic the tear turnover. [78, 79, 83] Herein we designed an ex vivo porcine eye infection model, in which culture medium was dripped onto each eye at a rate of four 25 μL drops/min to represent the tear turnover in vivo.…”
Section: Resultsmentioning
confidence: 99%
“…1 ). Since chinchilla TMs in OCT images were steeply angled, the orthogonal thickness was corrected for a refractive index (RI) error by computing the incident angle on the TM, assuming the RI of 1.44 40 . The thickness from around 100 consecutive points in each image was used to calculate the overall TM thickness.…”
Section: Methodsmentioning
confidence: 99%
“…Mass-produced soft contact lenses typically have one of several types of edge profiles, and some of these may have an impact on fitting, comfort and/or ocular surface health [107][108][109][110][111]. One study showed that hydrogel lenses with a greater edge thickness were associated with more movement than hydrogel lenses with a thinner edge [99].…”
Section: Edge Profilementioning
confidence: 99%